SISTEM PENGENDALIAN INTERN (SPI) TERHADAP PERSEDIAAN OBAT UNTUK PASIEN BADAN PENYELENGGARAAN JAMINAN SOSIAL (BPJS) DI UPT PUSKESMAS KOWEL - Fajar, Achmarul; Suprapto, Helman; Qonita, Ana Mara (Fakultas Ekonomi, Program Studi Akuntansi, 2017)
Puskesmas is a technical implementation unit of regency or city health service responsible for conducting health development in a work area. The main activity of the puskesmas is to sell care services, but the patient's treatment will not be maximized if the medicines owned by the puskesmas are incomplete. Therefore, the treatment of drug supply accounting must be applied by the puskesmas to assist smoothness in its operational activities. Without supplies, puskesmas are exposed to the risks of not being able to meet the needs of users of puskesmas (patient) services. The purpose of this study is to find out how the application of the Internal Control System to the supply of medicines for BPJS patients in UPT. Puskesmas Kowel. Inventories are particularly vulnerable to damage or theft. Therefore, internal control is required to protect the stock of the drug as well as to make inventory information more reliable. The result of the research shows that Puskesmas Kowel has implemented Internal Control System properly and correctly. Although not exactly the same as the theory because the Puskesmas Kowel is not a company, but it can be said Kowel Health Center has done criteria of internal control.